Agronomic options for higher crop growth, yield and soil fertility in upland cotton (Gossypium hirsutum) through in situ management of plant wastes in south zone - PRAHARAJ, C S; SANKARANARAYANAN, K; GOPALAKRISHNAN, N; RAJENDRAN, T P (The Indian Journal of Agricultural Sciences, 2010)
A field experiment was undertaken during 2004–07 in ‘Surabhi’ upland cotton (Gossypium hirsutum L.) at Coimbatore (Tamil Nadu) under irrigated condition to explore the suitability of locally available and low-cost plant wastes, viz neem, grass, weed and cotton residues vis-à-vis farmyard manure. The treatments to ridge planted cotton included insitu interrow (furrow) mulching and subsequent incorporation of whole cotton crop residues and ex-situ incorporation of locally available sun-dried plant wastes, such as neem (Azadirachta indica A. Juss) leaves, tree leaves (Trianthema portulacastrum L.), desert weeds (Horsepurslane or itsit), congress grass (Parthenium hysterophorus L.), field grass (mostly Cynodon dactylon L.), cotton stalks and farmyard manure (all @ 5 tonnes/ha in combination with a soil testbased recommended NPK dose of 60:13:25 kg/ha along with double controls (no NPK and no residues, only NPK). Results revealed that application of neem leaves @ 5 tonnes/ha was superior in respect of many performance parameters over both double controls, and was found to be equally effective to that of farmyard manure @ 5 tonnes/ha. Higher productivity in neem-amended plots was also due to increase in yield attributes, such as burst boils and seed cotton/ plant, boll weight and petiole N% at 90 days after planting because of integrated nutrient option. Thus, fibre productivity efficiencies were higher in neem-amended plots over the control (41%) and NPK alone (13.7%). Highest agronomic efficiency (10.2 kg/kg) and efficiency ratio (27.7 kg/kg) were also observed under it owing to greater nutrient assimilation efficiency (higher dry weight gained/kg NPK removed over and above control). Quality of fibre measured by high volume instrument did not show the differences due to the treatments. Plant wastes-amended plots influenced organic carbon, available N and K in soil leading to higher residual fertility although a crop of Sorghum grown after cotton in its residual fertility was not influenced by the treatments. Maximum economic benefits were also obtained with easily decomposable bio-wastes, like neem or grass cover over that in control, NPK and farmyard manure.